2021
DOI: 10.1111/pde.14799
|View full text |Cite
|
Sign up to set email alerts
|

Experience using dupilumab for pediatric atopic dermatitis at a tertiary care c enter: Inadequate response and adverse events

Abstract: Background/Objective: Dupilumab is highly effective in treating atopic dermatitis (AD). However, some patients experience difficulties with dupilumab therapy, such as inadequate clinical response, failure to achieve long-term disease control, or adverse events (AEs). Our objective is to assess inadequate response and AEs occurring in children on dupilumab therapy for AD.Methods: This is a retrospective cohort study of children on dupilumab for AD.Collected variables included patient demographics, medical histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
4
7
0
Order By: Relevance
“…[4][5][6][7][21][22][23][24][25][26][27] The prevalence of reported conjunctivitis was 6.7%-14.8% in clinical trials 5.6%-17.0% in other daily practice studies, which is quite similar to our results (16.4%). [4][5][6][7][21][22][23][24][25][26][27] Ariëns et al found that 34.1% of the adult patients developed conjunctivitis. Based on this study, conjunctivitis seems more common in adults than in children treated with dupilumab for AD in daily practice.…”
Section: (A) (B) (C)supporting
confidence: 91%
See 1 more Smart Citation
“…[4][5][6][7][21][22][23][24][25][26][27] The prevalence of reported conjunctivitis was 6.7%-14.8% in clinical trials 5.6%-17.0% in other daily practice studies, which is quite similar to our results (16.4%). [4][5][6][7][21][22][23][24][25][26][27] Ariëns et al found that 34.1% of the adult patients developed conjunctivitis. Based on this study, conjunctivitis seems more common in adults than in children treated with dupilumab for AD in daily practice.…”
Section: (A) (B) (C)supporting
confidence: 91%
“…All of these studies found a significant improvement of AD severity during dupilumab treatment. 21 , 22 , 23 , 24 , 25 , 26 , 27 After 16–24 weeks of treatment, EASI‐50 was achieved by 67.0%–99.3% of the patients. 21 , 23 , 24 EASI‐75 was achieved by 42.0%–66.7% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data exposed have shown a general improvement of disease severity scores and quality of life, even if below the line of LIBERTY AD PEDS. 1 Our population consisted of a majority of children under systemic immunosuppressants and included two patients who developed not only a known AE, 9 namely, facial redness, but also a SAE, which required hospitalization. These observational data should be validated by larger studies.…”
mentioning
confidence: 99%
“…In fact, a larger regimen (Table 3) was partly administrated in our cohorts, which might further prove dupilumab a safe choice in pediatric patients, considering the low occurrence of adverse events. Conjunctivitis was the most commonly reported AE, with incidence rates in real-life studies ranging from 4.95% to 12.15% [12,[19][20][21][22][23][24], which was observed in 5.1% patients in our study. In the ≥2 to <6 years old group, one child experienced the injection-site reaction after the 2 nd injection, which resolved by itself.…”
Section: Discussionmentioning
confidence: 51%